Bacterial Pigments: Sustainable Compounds With Market Potential for Pharma and Food Industry - Venil, Chidambaram Kulandaisamy; Dufossé, Laurent; Renuka Devi, Ponnuswamy (Frontiers in Sustainable Food Systems, 2020)
The continued universal application of synthetic colorants for decades have caused environmental pollutions and human health vulnerabilities. So, it was indispensable to discover novel natural colorants such as microbial colorants which were safer and better than synthetic colorants. The potential of bacterial pigments for mass production of diversified coloring properties was first prospective and is now getting the notable importance and attention of both the researchers and industries. Literature establishes that the natural colorants produced from microbes were applied in food and pharma products successfully. Apart from serving as food colorants, bacterial pigments have several pharmacological activities like anti-microbial, anti-cancer, anti-oxidant, anti-inflammatory and anti-allergic properties with large economic potential. And, there is vast scope for easy and cheap production of natural colorants in all seasons from bacterial sources, compared to plant sources. Tactics in strain improvement, fermentation conditions, metabolic engineering, and easy extraction techniques are needed to produce high end products. This review highlights the significance of bacterial colorants and summarizes its application in food and pharma industries. Further, the major challenge of lower stability of bacterial pigments and the solution to address it is also appraised.